2017
DOI: 10.1016/j.ultsonch.2017.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Interactions at the planar Ag3Sn/liquid Sn interface under ultrasonic irradiation

Abstract: The interactions at the interface between planar AgSn and liquid Sn under ultrasonic irradiation were investigated. An intensive thermal grooving process occurred at AgSn grain boundaries due to ultrasonic effects. Without ultrasonic application, planar shape of AgSn layer gradually evolved into scalloped morphology after the solid-state Sn melting, due to a preferential dissolution of the intermetallic compounds from the regions at grain boundaries, which left behind the grooves embedding in the AgSn layer. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, a few Ni 3 Sn 4 chunks were distributed in the joint (marked by yellow circles). Shao et al (2017) observed the same appearance of grooves at the planar Ag 3 Sn layer under the effect of USV. They suggested that the formation of grooves may have been mainly attributable to acoustic cavitation and streaming effects on the accelerated dissolution of Ag 3 Sn at grain boundaries.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, a few Ni 3 Sn 4 chunks were distributed in the joint (marked by yellow circles). Shao et al (2017) observed the same appearance of grooves at the planar Ag 3 Sn layer under the effect of USV. They suggested that the formation of grooves may have been mainly attributable to acoustic cavitation and streaming effects on the accelerated dissolution of Ag 3 Sn at grain boundaries.…”
Section: Resultsmentioning
confidence: 57%
“…Therefore, the Ni particles in the joint could completely react with Sn for a short time to produce a complete IMC joint. Shao et al (2017) and Li et al (2017) also fabricated sole IMC joints in a short time using an ultrasound-induced transient liquid phase bonding process. These studies indicated that the rapid formation of sole IMC joints was attributable to the accelerated dissolution of the substrate into the liquid solder, which was induced by complex sonochemical effects (ultrasonic cavitation and ultrasonic streaming) on the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…7c). It is believed that the formation of the groove is due to IMC dissolution at Ag 3 Sn grain boundaries; the IMC at grain boundaries continually dissolved into the molten solder, deepening the grooves and inducing silver leaching [14,15]. The silica NPs located at grain boundaries can hinder the dissolution of the IMC by the molten solder along grain boundaries and hence retard silver leaching.…”
Section: Resultsmentioning
confidence: 99%